2021
DOI: 10.3389/fcomm.2021.651769
|View full text |Cite
|
Sign up to set email alerts
|

Text Complexity Modulates Cross-Linguistic Sentence Integration in L2 Reading

Abstract: Cross-linguistic influences (CLI) in first-language (L1) and second-language (L2) reading have been widely demonstrated in experimental paradigms with adults at the word and sentence levels. However, less is known about CLI in adolescents during naturalistic text reading. Through eye-tracking and behavioral measures, this study investigated expository reading in functionally English monolingual and Spanish (L1) - English (L2) bilingual adolescents. In particular, we examined the role of L1 (Spanish) sentence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…Table 2 summarizes the aforementioned eye movement measures to capture participants’ cognitive processes and mental efforts. According to previous research 17 , 31 , 64 , four of these measures were lexical ones in the early stage , reflecting unconscious word recognition, lexical access, and automatic text processing. They are measures of the first pass eye movements at word-level, including First Fixation Duration, First Pass Dwell Time, First Pass Saccade Amplitude, and First Pass Dwell Time before Skipped Words.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…Table 2 summarizes the aforementioned eye movement measures to capture participants’ cognitive processes and mental efforts. According to previous research 17 , 31 , 64 , four of these measures were lexical ones in the early stage , reflecting unconscious word recognition, lexical access, and automatic text processing. They are measures of the first pass eye movements at word-level, including First Fixation Duration, First Pass Dwell Time, First Pass Saccade Amplitude, and First Pass Dwell Time before Skipped Words.…”
Section: Methodsmentioning
confidence: 93%
“… Measures Description Implications on learning/cognition Lexical processing stage First fixation duration Length of time spent on first fixating on a word These four measures are at local word-level. Longer fixation and dwell time and shorter saccade amplitude at this level can reflect increased cognitive load in unconscious word recognition, lexical access, and automatic text processing 17 , 31 , 64 First pass dwell time Aggregated duration of all first pass fixations on a word First pass saccade amplitude Amplitude of the first saccade into a word First pass dwell time before skipped words Summed durations of all first pass fixations on a word that is directly before skipped words Post-lexical processing stage Total fixation count Total number of fixations on each passage These four measures are at global passage-level. More fixations and regressions, longer fixation duration, and lower word skipping rate at this level can reflect increased cognitive load in conscious information integration and controlled processing 17 , 31 , 64 Total fixation duration Aggregated fixation durations of each passage Total regression count Number of all inter-word regressions within a passage Total word skipping rate Number of skipped words divided by total count of words in a passage Other Change of pupil size Difference between average pupil size and pupil size baseline divided by pupil size baseline in a passage Change of pupil size can indicate arousal, stress, and mental workload 15 , 52 , 60 , 61 Blink rate Number of blinks per minute Blink rate can indicate mental workload, fatigue, and state of attention …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Kim et al (2018) found that high (versus low) skilled multilingual L2 readers were faster to process L2 words, particularly when reading simplified texts (simplified for text cohesion, lexical complexity, and syntactic complexity). Similarly, Leon-Guerrero et al (2021) found that adolescent multilinguals reading L2 educational texts could overcome cross-linguistic intrusions as a function of their syntactic integration skills, semantic knowledge, and text complexity. Thus, comprehension of L2 texts might not solely depend on L2-specific word knowledge, but also on L1 reading skills for syntactically complex texts (also see, Yamasaki & Prat, 2021).…”
Section: Psycholinguistic Approaches To Multilingual Readingmentioning
confidence: 92%